Estudio de la participación del gen YUCCA4 en la regulación del crecimiento y desarrollo de Arabidopsis thaliana - Munguía Rodríguez, Aarón Giovanni (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
Plants integrate diverse environmental stimuli to control their growth and development. These processes are under the control of substances known as phytohormones or plant growth regulators whose action mechanisms have been investigated using Arabidopsis thaliana as a biological model. The most studied plant hormones are the auxins, represented by indole-3-acetic acid (IAA), which is involved in most plant growth and developmental processes. IAA biosynthesis can occur via two pathways: tryptophan (Trp)-independent and Trp-dependent. The existence of four different pathways in the IAA Trp- dependent pathway has been postulated, and among them, the most important is the indole-3-pyruvic acid (IPA) pathway where flavin-dependent monooxygenases encoded by YUCCA genes convert IPA into AIA. The existence of 11 YUCCA genes has been reported in the Arabidopsis genome, loss of function mutations affecting one or more YUCCA genes reveal its importance on IAA biosynthesis and functional redundancy. However, this redundancy limits our understanding of the precise function of these proteins in planta. Another strategy for studying redundant genes is through gain of function studies using plants that express gene constructs aimed at increasing the expression of endogenous genes such as activation tagging or by expressing selected genes under control of strong and constitutive promoters. In this research, the participation of YUCCA4 gene in regulating growth and development of Arabidopsis thaliana was investigated using thread/yuc4, an activation tagging mutant likely overexpressing YUCCA4 and transgenic lines that overexpress this gene.

Las plantas son organismos que integran diversos estímulos ambientales para controlar su crecimiento y desarrollo, dichos procesos están bajo el control de diferentes sustancias conocidas como fitohormonas o reguladores del crecimiento vegetal cuyos mecanismos de acción se han definido gracias al empleo de Arabidopsis thaliana como modelo biológico. Las hormonas vegetales más estudiadas son las auxinas, representadas principalmente por el ácido indol-3-acético (AIA), el cual está implicado en prácticamente todos los procesos de regulación del crecimiento y desarrollo vegetal. La biosíntesis del AIA puede ser a través de dos vías: la triptófano (Trp)-independiente y la Trp-dependiente. En la biosíntesis del AIA Trp- dependiente, se ha postulado la existencia de cuatro rutas distintas, siendo la más importante la que involucra al ácido indol-3-pirúvico (IPA) donde las monooxigensas dependientes de flavina codificadas por los genes YUCCA convierten al IPA en el AIA. Se ha descrito que existen 11 genes YUCCA en el genoma de Arabidopsis, mutaciones con pérdida de función en uno o varios de estos genes ponen de manifiesto su importancia en la biosíntesis del AIA y la existencia de redundancia funcional. Otra estrategia para estudiar este tipo de genes es a través de métodos de sobreexpresión que producen niveles incrementados de transcrito y/o proteína dando como resultado fenotipos de ganancia de función asociados con dicho cambio. En el presente trabajo se investigó́ la participación del gen YUCCA4 en la regulación del crecimiento y desarrollo de Arabidopsis utilizando una mutante generada por una inserción de T-DNA que porta activadores transcripcionales (activation tagging) y líneas transgénicas de sobrexpresión.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias en Biología Experimental
Keywords: info:eu-repo/classification/cti/6; IIQB-M-2014-0380; Auxinas; Gen; Crecimiento; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3904